Stability Analysis of A Non Vaccinated Sir Epidemic Model (International Journal of Engineering and Computer Science, 2015)
A proper mathematical model structure is required to understand the dynamics of the spread of infectious diseases. In this paper I have discussed about a general SIR epidemic model which represents the direct transmission of infectious disease. Local and global stabilities of both the disease free and the endemic equilibrium are derived by using the evaluated reproduction number.